Applied Sport Psychologie : personal growth to peak performance - Williams, Jean M., ....-; Krane Vikki, ....- (New York : MCGraw-Hill Education, 2021)
Your grades. Your time. Make the most of it. You want to achieve the best grades possible with the limited time you have to study. McGraw-Hill Connect helps you do just that. Connect is your personalized digital learning assistant that makes earning better grades and managing time easier, quicker, and more convenient than ever.
Keywords: Sport Psychologie